El Excentrico, 1968-09-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 20, 1968 [20 de septiembre de 1968]. No volume or issue number. Cover has a photograph of Poche, who was running for assemblyman for the 25th District.